Cooling Panel with Integrated PCM Layer: A Verified Simulation Study - Renars Millers; Aleksandrs Korjakins; Arturs Lešinskis; Anatolijs Borodinecs (Energies, 2020)
The focus of this research paper is to develop a verified simulation model for a cooling panel with integrated phase-change materials (PCMs)—a stainless steel panel filled with PCM and integrated hydronic piping circuit. This solution is targeted for passive cooling of residential buildings in Baltic Sea region that experience overheating for most of the year due to highly insulated building envelopes and extensive glazing—a phenomena for nearly zero energy buildings (NZEBs). This approach aims to maintain comfortable indoor temperature all year round by passive means—free-cooling, adiabatic (evaporative) cooling or limited mechanical cooling. The simulations are performed with IDA ICE 4.8 and the measurements for simulation model verification are collected from a test chamber. The results show that reasonable agreement can be reached for simulated and experimentally measured data.